Overcoming basis risk in agricultural index insurance using crop simulation modeling and satellite crop phenology - Afshar, Mehdi H.; Foster, Tim; Higginbottom, Thomas P.; Parkes, Ben; Hufkens, Koen; Mansabdar, Sanjay; Ceballos, Francisco; Kramer, Berber (EGU General Assembly, 2021)
Extreme weather causes substantial damage to livelihoods of smallholder farmers globally and are projected to become more frequent in the coming decades as a result of climate change. Index insurance can theoretically help farmers to adapt and mitigate the risks posed by extreme weather events, providing a financial safety net in the event of crop damage or harvest failure. However, uptake of index insurance in practice has lagged far behind expectations. A key reason is that many existing index insurance products suffer from high levels of basis risk, where insurance payouts correlate poorly with actual crop losses due to deficiencies in the underlying index relationship, contract structure or data used to trigger insurance payouts to farmers.